(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
This article aimed to discuss the real role of technology in the welfare of farm animals. In this sense, modern biotechnology techniques for the purposes of substitute products for those of animal origin or even free of slaughter, smart farms and, finally, scientific research on genetic engineering in this category of animals exploited for food were analyzed. The methodology versed was a theoretical research. Based on the binomial, increased productivity and improved animal welfare, the technologies addressed, still relatively incipient, were dubious in terms of increasing productivity and certainly opposed to animal welfare. In exceptional vegan alternatives to meat, milk, eggs and honey, it is true that technology has resulted in worsening animal welfare, even due to the unquestionable continuity of intensive livestock farming and disrespect for animal rights. The technology also did not definitively answer other secondary issues posed such as environmental preservation and smart farms, human health and transgenic animals, patenting of life, Social Justice, etc. In this context, no other threat to animal protection is as dangerous as genetic engineering that intends to design animals without pain, insensitive and non-sentient for use in livestock. With a misguided discourse that, after all, recognizes the sentience of production animals and then, without any prior and comprehensive ethical debate, aims at their genetic modification into a insensitive thing, intends to keep the exploitation of animals for human consumption, convincing, once again, public opinion that animals do not suffer. In addition to the immorality of a technology designed for the impoverishment of worthy and sentient beings, however, it remains intricate positioning for animal defense based on animal suffering as one of its capital arguments. Thus, technology imposes original challenges to be urgently faced by animal law.